MORPHO-FUNCTIONAL CHARACTERISTIC OF NEURONS OF MOTOR SEGMENTAL CENTRES OF ISCHIATIC NERVE BY VINCRISTINE- AND ETIOPOSIDE-INDUCED PERIPHERAL NEUROPATHY - Геращенко, С. Б.; Дельцова, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Influence of the vincristinе (86 white rats) and etoposidе (86 white rats) has studied in experiment. Вy vincristinе-induced neuropathy сhanges of perikarions of motor neurons of the spinal cord thus nonspecific reaction of the nerve cell body were established Experimental etoposide-induced neuropathy is peripheral progressive axonopathy. The processes of alteration and compensation were combined. By all terms of observation the pathomorphological pictures were heterogeneous and mosaic.